Patients' perception of colonoscopy and acceptance of colonoscopy based IBD related colorectal cancer surveillance. (1st February 2021) - Braithwaite, Eve; Carbonell, Jenelyn; Kane, John S.; Gracie, David; Selinger, Christian P.
ABSTRACT: Objectives: Patients with Inflammatory Bowel Disease (IBD) are at an increased risk of colorectal cancer (CRC). Current surveillance for CRC involves often uncomfortable colonoscopy. To assess IBD patients' perception of colonoscopy and examine preferences for hypothetical alternatives. Methods: IBD patients in clinical remission rated acceptable frequency of colonoscopy and hypothetical alternatives to colonoscopy-based surveillance (preference of yearly blood, yearly stool or 5-yearly imaging tests over 5-yearly colonoscopy). Participants rated discomfort of the last colonoscopy was compared with hospital records. Results: Of 282 patients with recollection of colonoscopy 65.8% rated the discomfort as moderate to severe, which correlated weakly with endoscopists' perception (r = 0.225; p = 0.015). There were no significant differences in patients' or endoscopists' perceptions of discomfort between sedated and unsedated colonoscopies. Undergoing a yearly colonoscopy was acceptable to 49.5%. Experienced discomfort did not correlate with patients' views on acceptable frequency of surveillance colonoscopy. Over 95% of patients would prefer blood, stool, or imaging tests over colonoscopy but nearly half expected sensitivities ≥95%. Conclusion: A large proportion of IBD patients experienced colonoscopy as moderate to severely uncomfortable but would still accept colonoscopy surveillance frequency according to current guidance. Participants expected sensitivities ≥95% for potential alternatives to colonoscopy-based surveillance programs. Expert Opinion: IBD patients frequently experience colonoscopy as uncomfortable but accept colonoscopy as the gold standard for colorectal cancer surveillance. The currently suggested frequencies of surveillance by colonoscopy are acceptable to IBD patients. They do however express a clear preference for non-invasive surveillance techniques. Some promising initial results have been obtained based on faecal or blood sampling. However, these have yet to be tested in large prospective studies to determine their sensitivity and specificity. IBD patients expect these non-invasive tests to meet high standards for sensitivity. In our view it is feasible that analogue to faecal immunochemistry based testing for general population bowel cancer screening non-invasive IBD surveillance techniques will emerge. This could lead to a reduction in the need for colonoscopy to those testing positive on faecal or blood based surveillance.